Advancing 21st-Century Creativity and Innovation into Japanese Educational System - Adeoye, Moses Adeleke (Universitas Pendidikan Indonesia (Indonesia University of Education), 2023)
The 21st century requires a new set of skills for success in a global economy. Creativity and innovation are essential components of skills, yet the current Japanese educational system does not place a strong emphasis on these skills. This paper stated the importance of project-based learning and technology integration approaches that can be used to advance creativity and innovation in the Japanese educational system. By promoting creativity and innovation in the Japanese educational system, we can help to develop critical thinking, problem-solving, and collaboration skills that are essential for success in the 21st century. The paper provides detailed strategies for overcoming challenges in advancing 21st-century creativity and innovation in the Japanese educational system. Finally, the paper emphasizes the importance of providing teachers with the necessary training and support to implement innovative approaches effectively.